Randomized Cost-Effectiveness Trial of Group Interpersonal Psychotherapy (IPT) for Prisoners With Major Depression - Johnson, J.; Stout, R.; Miller, Ted; Zlotnick, C.; Cerbo, L.; Andrade, J.; Nargiso, J.; Bonner, J.; Wiltsey-Stirman, S. (American Psychological Association, 2019)
Objective: This study tested the effectiveness and cost-effectiveness of interpersonal psychotherapy (IPT) for major depressive disorder (MDD) among prisoners. It is the first fully powered randomized trial of any treatment (pharmacological or psychosocial) targeting MDD among incarcerated individuals. Method: One hundred eighty-one male (n = 117) and female (n = 64) prisoners from prison facilities in 2 states were randomized to group IPT (delivered by master's-level and nonspecialist prison counselors) for MDD plus prison treatment as usual (TAU) or to TAU alone. Participants' average age was 39 (range = 20 - 61); 20% were African American and 19% were Hispanic. Outcomes assessed at posttreatment and 3-month follow-up included depressive symptoms (primary; assessed using the Hamilton Rating Scale for Depression), suicidality (assessed with the Beck Scale for Suicide Ideation and Beck Hopelessness Scale), in-prison functioning (i.e., enrollment in correctional programs; discipline reports; aggression/victimization; and social support), remission from MDD, and posttraumatic stress disorder symptoms. Results: IPT reduced depressive symptoms, hopelessness, and posttraumatic stress disorder symptoms, and increased rates of MDD remission relative to prison TAU alone. Effects on hopelessness were particularly strong. Cost per patient was $2,054 including costs for IPT training and supervision or $575 without these costs. For providers running their second or subsequent IPT group, cost per additional week in remission from MDD (relative to TAU alone) was $524 ($148 excluding training and supervision costs, which would not be needed for established programs). Conclusions: IPT is effective and cost-effective and we recommend its use for MDD among prisoners. It is currently the only treatment for MDD evaluated among incarcerated individuals.